Artificial Intelligence in Mathematics Education: Trends, Challenges, and Opportunities - Tang, William Ko-Wai (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This paper examines the transformative influence of artificial intelligence (AI) on mathematics education. It delineates the evolution of educational technology, progressing from basic computational tools to advanced AI-driven systems that enhance personalised learning experiences. The study highlights how AI adapt to individual student needs, increase engagement, and promote deeper understanding of mathematical concepts by analysing contemporary trends such as intelligent tutoring systems, automated assessments, and personalised learning platforms. Additionally, it explores the potential of AI to foster inclusive learning environments, particularly for students with special needs. The paper also considers challenges related to infrastructure, teacher preparedness, and equity in AI implementation, alongside future directions for research and innovation in the application of AI within mathematics education.